2011
DOI: 10.1007/s11242-011-9767-0
|View full text |Cite
|
Sign up to set email alerts
|

A Discussion of the Effect of Tortuosity on the Capillary Imbibition in Porous Media

Abstract: In the past decades, there was considerable controversy over the LucasWashburn (LW) equation widely applied in capillary imbibition kinetics. Many experimental results showed that the time exponent of the LW equation is less than 0.5. Based on the tortuous capillary model and fractal geometry, the effect of tortuosity on the capillary imbibition in wetting porous media is discussed in this article. The average height growth of wetting liquid in porous media driven by capillary force following the L s (t) ∼ t 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
194
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 387 publications
(199 citation statements)
references
References 53 publications
(65 reference statements)
4
194
1
Order By: Relevance
“…However, some recent literature reported that the time exponent was not always 0.5. Cai and Yu (2011) introduced fractal to characterize the tortuosity of imbibition streamline, and theoretically found that the time exponent was related to tortuosity fractal dimension. Hu et al (2012) demonstrated that the time exponent can reflect the pore connectivity of the tight rock.…”
Section: Completely Counter-current Imbibitionmentioning
confidence: 99%
“…However, some recent literature reported that the time exponent was not always 0.5. Cai and Yu (2011) introduced fractal to characterize the tortuosity of imbibition streamline, and theoretically found that the time exponent was related to tortuosity fractal dimension. Hu et al (2012) demonstrated that the time exponent can reflect the pore connectivity of the tight rock.…”
Section: Completely Counter-current Imbibitionmentioning
confidence: 99%
“…To directly calculate n value, the above curve is sometimes described in logarithmic coordinates; at this point, the imbibition index n manifests as the slope of a straight line segment on the curve in logarithmic coordinates. On the theoretical SI mechanism, Cai and Yu (2011) defined n as imbibition time exponent. It is worth noting that the exponent n is analytically expressed as a function of tortuosity fractal dimension, and in the range of 1/6e1/2 in Cai and Yu's fractal model.…”
Section: Basic Representative Elementary Structurementioning
confidence: 99%
“…Specifically, pore-connectivity effects, and consequently, phase trapping, residual saturations, and hysteresis have been disregarded in the straight tube-bundle models. Tortuous flow path with variably shaped apertures or with variable lengths have successfully been derived and applied in the flow properties characterization using fractal based approach (Cai and Yu, 2011;Cai et al, 2014a;Liu et al, 2016b). Thus, application of simple physical theory to simulate a capillary curve in a complex, irregular and disordered pore space is a missing requirement.…”
Section: Capillary Pressure Curves From Pore-scale Modelingmentioning
confidence: 99%